Actively Managed Investment Portfolio Dilemmas, ‘Lost Returns Approach’ - Elmesseary, Mohamed (European Journal of Sustainable Development, 2014)
Extending the basic belief on which the investment management business is built upon: Professional managers can beat the market; linking within a practical approach between the academics’ views and practitioners’ opinions regarding the market beating inability and the reasons from behind; paying some more attention to the returns, managers lose due to their insufficient active strategies; this work analyzes the past performance of the whole stocks that actually traded in the Egyptian market between June, 2007 and June, 2012 in order to measure how fund managers are geniuses by the zero returns they lose. It performs T-test among three types of portfolios, a well-known market index, the funds’ portfolios, and the best actively managed portfolio that can be built and used as a restrict criterion. The findings reveal that adopting the simple thought of naïve investors, away from the portfolio optimization possibilities, do generate the active portfolio, which is economically optimized, as the investors initial resources are not only significantly sufficient for accessing its investments, but can be also recovered with no more than 3 months. And which can significantly out-perform the comparable benchmarks, but unfortunately, the fund managers are not geniuses due to the impressive returns they lose. JEL classification: G1; G2 Keywords: Capital markets, mutual funds, performance evaluation, market timing ability, stock picking ability